A Facile, Multifunctional, Transparent, and Superhydrophobic Coating Based on a Nanoscale Porous Structure Spontaneously Assembled from Branched Silica Nanoparticles. Issue 13 (23rd July 2015) - Li, Fang; Du, Miao; Zheng, Zhong; Song, Yihu; Zheng, Qiang
<x xml:space="preserve">Abstract</x> An ideal nanoscale porous structure for both transparency and superhydrophobicity is proposed and achieved by the spontaneous assembling of branched silica nanoparticles during wipe‐coating, based on the analysis of current research status and actual requirements. Multifunctional transparent and superhydrophobic coatings with water impinging resistance, long‐time water repellency, renewability, and temperature stability are fabricated on a series of material surfaces.